Introgressive hybridization erodes morphological divergence between lentic and lotic habitats in an endangered minnow. Issue 19 (15th September 2021) - Baker, Henry K.; Hankins, Danielle C.; Shurin, Jonathan B.
Abstract: Introgressive hybridization may erode phenotypic divergence along environmental gradients, collapsing locally adapted populations into a hybrid swarm. Alternatively, introgression may promote phenotypic divergence by providing variation on which natural selection can act. In freshwater fishes, water flow often selects for divergent morphological traits in lake versus stream habitats. We tested the effects of introgression on lake–stream morphological divergence in the minnow Owens Tui Chub ( Siphateles bicolor snyderi ), which has been rendered endangered by introgession from the introduced Lahontan Tui Chub ( Siphateles bicolor obesa ). Using geometric morphometric analysis of 457 individual Tui Chub from thirteen populations, we found that both native and introgressing parent taxa exhibited divergent body and caudal fin shapes in lake versus stream habitats, but their trajectories of divergence were distinct. In contrast, introgressed populations exhibited intermediate body and caudal fin shapes that were not differentiated by habitat type, indicating that introgression has eroded phenotypic divergence along the lentic–lotic gradient throughout the historic range of the Owens Tui Chub. Individuals within hybrid populations were less morphologically variable than those within parent populations, suggesting hybrid adaptation to selective agents other than water flow or loss of variance by drift. Abstract : Introgressive hybridization can either erode or promote adaptive phenotypic divergence along environmental gradients. We tested the effects of widespread introgressive hybridization on morphological divergence between lake and stream habitats in the minnow Tui Chub. We found that hybridization has eroded morphological divergence, but comparisons of morphological variance between parent and hybrid populations suggest this outcome may not be maladaptive.